Augmented human : how technology is shaping the new reality - Papagiannis, Helen (O'Reilly Media, 2017)
"Augmented Reality (AR) blurs the boundary between the physical and digital worlds. In AR's current exploration phase, innovators are beginning to create compelling and contextually rich applications that enhance a user's everyday experiences. In this book, Dr. Helen Papagiannis--a world-leading expert in the field--introduces you to AR: how it's evolving, where the opportunities are, and where it's headed. If you're a designer, developer, entrepreneur, student, educator, business leader, artist, or simply curious about AR's possibilities, this insightful guide explains how you can become involved with an exciting, fast-moving technology. You'll explore how: Computer vision, machine learning, cameras, sensors, and wearables change the way you see the world Haptic technology syncs what you see with how something feels Augmented sound and hearables alter the way you listen to your environment Digital smell and taste augment the way you share and receive information New approaches to storytelling immerse and engage users more deeply Users can augment their bodies with electronic textiles, embedded technology, and brain-controlled interfaces Human avatars can learn our behaviors and act on our behalf"--ProQuest